2005
DOI: 10.1007/s00339-004-3059-2
|View full text |Cite
|
Sign up to set email alerts
|

Infrared femtosecond laser ablation of graphite in high vacuum probed by optical emission spectroscopy

Abstract: We report infrared, ultra-short (780 nm, 120 fs) laser ablation of graphite in high vacuum. The plume characteristics are analyzed by wavelength-, time-, and spatially resolved optical emission spectroscopy. A multi-component structure of the plume is observed as a function of time, space, and laser fluence: (i) line emission from electronically excited carbon neutrals and ions; (ii) luminescence from excited C-3 radicals; (iii) broadband visible radiation, ascribed to black-body-like emission from larger carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…At both the fluences used, it can be observed a strong segregation of the species, with molecules going slower than the neutral C, C þ going faster, and the C 2 þ component being the fastest, as reported earlier [68]. The apparition of all those species, in this order, confirms molecular dynamics calculations [69].…”
Section: Temporal Pulse Laser Shaping For Diamond-like Carbon Films Dsupporting
confidence: 86%
“…At both the fluences used, it can be observed a strong segregation of the species, with molecules going slower than the neutral C, C þ going faster, and the C 2 þ component being the fastest, as reported earlier [68]. The apparition of all those species, in this order, confirms molecular dynamics calculations [69].…”
Section: Temporal Pulse Laser Shaping For Diamond-like Carbon Films Dsupporting
confidence: 86%
“…These include C 60 (Mitzner & Campbell 1995;Andersen et al 1996;Hesler et al 1997;Wen et al 1998), carbon clusters (Rohlfing 1988;Amoruso et al 2005), and metal clusters as small as Al 4 − (Frenzel et al 1997;Walther et al 1997;Toker et al 2007). Emission of blackbody radiation has also been shown to be an important cooling mechanism in highly excited C 60 (Andersen et al 1997;Hansen & Echt 1997), C 60 + (Vostrikov et al 2000), fullerene anions (Andersen et al 1997), small carbon clusters (Shinozaki et al 2002;Amoruso et al 2005), and napththalene molecules (Beck et al 1981).…”
Section: Blackbody Emission From Molecules and Clustersmentioning
confidence: 99%
“…Although spectra of individual molecules are shown elsewhere (Mitzner & Campbell 1995;Andersen et al 1996;Wen et al 1998;Rohlfing 1988;Amoruso et al 2005), this spectrum is shown here because it illustrates the emission observed from carbon particles having a range of structures and with different particle sizes. The spectrum in Figure 1 is then the blackbody emission of the sample modified by the overall average emissivity of these particles.…”
Section: Blackbody Emission From Molecules and Clustersmentioning
confidence: 99%
“…This conclusion is supported by recent measurements of the plume dynamics, in vacuum, after fs infrared ablation of graphite, where plumes with multi-component velocity structures were also observed. 35,36 It is suggested that the first component is associated with an initial burst of highly energetic/electrically excited ablated components, indicative of the enhanced fraction of nonthermal ejection mechanisms compared to ns ablation, and the second with subsequently ejected, slower moving, material which could consist of thermally ejected C atoms and clusters. We suggest that the second wave forms as the material ejected more slowly collides with the back of the dissipating first shock wave.…”
Section: Time Resolved Imaging Of Plume Emissions From Specific Spmentioning
confidence: 99%